TWO DECADES OF REALISTIC MATHEMATICS EDUCATION RESEARCH IN INDONESIA: A SURVEY - Rully Charitas Indra Prahmana; Laela Sagita; Wahyu Hidayat; Niken Wahyu Utami (IKIP Siliwangi and I-MES, 2020)
Freudenthal's ideas on mathematics that stated mathematics as a human activity and mathematics must be connected to reality have colored towards learning mathematics all over the world, including Indonesia. Existing research on this topic in Indonesia among two decades is categorized and compared. This paper presents a systematic literature review of empirical studies on this learning approach in Indonesian context. The implementation of this approach in Indonesia was analyzed comprehensively and divided into several major topics. Resources of this research come from 110 articles by ten highest rank accredited journals by the Ministry of Research, Technology, and Higher Education, the Republic of Indonesia as an achievement for the peer-reviewed journal, which has excellent quality in management and publication. The results show that there are seven categories summarized in this research: the dominance of published RME articles, RME research subjects, mathematical topics, students' abilities, RME terms, and the research method used in RME articles. Lastly, the summarized 110 papers are displayed in the table to give essential information as a fundamental idea for further RME research.